Diabetes mellitus and chronic kidney disease in the Eastern Mediterranean region: findings from the Global Burden of Disease 2015 study - Moradi-Lakeh, Maziar; Bärnighausen, Till; Jonas, Jost B.; Mohammed, Shafiu (International journal of public health, 2017)
We used findings from the Global Burden of Disease 2015 study to update our previous publication on the burden of diabetes and chronic kidney disease due to diabetes (CKD-DM) during 1990-2015.
Gesehen am 05.05.2020